Investigating On the Quality of Wild Licorice Roots Collected from Different Regions of Iran - H Hajimehdipoor; Y Amanzadeh; T Hasanloo; M Shekarchi; Z Abedi; M Pirali Hamedani (Institue of Medicinal Plants, ACECR, 2008)
Background: Glycyrrhiza glabra L. has been used in respiratory diseases, gastric and duodenal ulcers and liver insufficiencies for many years. The plant grows in different regions of Iran. Since our country is considered one of the greatest exporting countries of the plant roots, investigation of licorice quality from different parts of Iran and determination of the best area for its growing seems to be important. Objective: According to validated references, glycyrrhizic acid percentage and water-soluble extractives are determinative of quality therefore, in this investigation, these two factors have been measured in the plants collected from different regions of Iran. Method: Roots of the plant were collected from Kerman, Kermanshah, Sirjan, Sarhadd (Fars province), Istahban (Fars province), Ghasredasht (Fars province), Najaf Abad (Isfahan province), Ganjnameh (Hamedan province), Ekbatan (Hamedan province), Mahabad, Khorram Abad and Ardabil and water-soluble extractives using maceration method and glycyrrhizic acid percentage with HPLC technique were determined in each sample. Results: The results showed that the amount of water-soluble extractives and glycyrrhizic acid are high in samples from Kermanshah, Sarhadd and Kerman while these two factors are the lowest in the plant roots collected from Ekbatan and Ganjnameh. Conclusion: The plant roots collected from Kermanshah, Sarhadd and Kerman have the highest quality and are the best for medicinal purposes, sweetening and flavoring agent and for exporting as well.